2022
DOI: 10.1002/jpen.2369
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial overgrowth assessment and treatment among pediatric intestinal rehabilitation and nutrition support providers: An international survey of clinical practice patterns

Abstract: Background Small bowel bacterial overgrowth (SBBO) is a common, but difficult to diagnose and treat, problem in pediatric short bowel syndrome (SBS). Lack of clinical consensus criteria and unknown sensitivity and specificity of bedside diagnosis makes research on this potential SBS disease modifier challenging. The objective of this research was to describe clinical care of SBBO among international intestinal rehabilitation and nutrition support (IR&NS) providers treating patients with SBS. Methods A secure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Characteristics of gut microbial community function and composition in IF have been studied with association to poor growth, ability to wean off PN, liver disease, and duration of intestinal adaptation (89,90). SBBO is a primarily clinical disorder of IF dysbiosis characterized by a variety of nonspecific and semi‐specific complaints and thought to occur with abnormally high concentrations of bacteria in the small bowel (91,92). In light of a large and growing body of literature suggesting an influence of ID and iron supplementation on microbial communities, as well as the theoretical potential for SBBO to create a high hepcidin state, clarity of the impact of this relationship as it specifically pertains to IF outcomes is an important near‐term need in assembling a larger understanding of iron in IF (93,94).…”
Section: Future Directionsmentioning
confidence: 99%
“…Characteristics of gut microbial community function and composition in IF have been studied with association to poor growth, ability to wean off PN, liver disease, and duration of intestinal adaptation (89,90). SBBO is a primarily clinical disorder of IF dysbiosis characterized by a variety of nonspecific and semi‐specific complaints and thought to occur with abnormally high concentrations of bacteria in the small bowel (91,92). In light of a large and growing body of literature suggesting an influence of ID and iron supplementation on microbial communities, as well as the theoretical potential for SBBO to create a high hepcidin state, clarity of the impact of this relationship as it specifically pertains to IF outcomes is an important near‐term need in assembling a larger understanding of iron in IF (93,94).…”
Section: Future Directionsmentioning
confidence: 99%
“…Although PIF may predispose to SBBO, the diagnosis is often difficult due to nonspecific symptoms and lack of consensus in the definition (18,19). In PIF, patients are often treated empirically for nonspecific symptoms (20). Heinzman and Cole (21) reported that one-third of patients with SBS were treated for SBBO, despite a diagnosis established by duodenal aspirate only occurring in 5% of patients.…”
Section: Table 3 Single Taxon Analysis Showing Increase In Microbial ...mentioning
confidence: 99%